Application of FRA to Improve the Design and Maintenance of Wireless Power Transfer Systems - Kim, Dowon; Abu-Siada, Ahmed; Sutinjo, Adrian (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
Frequency response analysis (FRA) plays an important role in the assessment of the mechanical integrity and hence, reliability of high-voltage power transformers. Wireless power transfer (WPT) system introduced by Tesla a 100 years ago based on Faraday's law of electromagnetic induction is similar to a conventional power transformer. Therefore, the reliability of a large WPT system can also be evaluated using FRA measurement. When the WPT system is constructed, the electrical components and the desired transfer distance need to be ascertained accurately. Furthermore, the structure of the winding and the electrical characteristic of the components in WPT systems may vary due to aging or fault events. FRA measurement can examine the discrepancy between the WPT system parameters and the reference fingerprint data to provide cost-effective condition monitoring-based maintenance scheme for the WPT systems. This paper presents a detailed circuit analysis of a two-coil inductively coupled WPT model in different compensating topologies to accomplish efficient energy transfer. Then, FRA measurement is used to detect the variation in the amplitude and the phase angle of the developed circuit input impedance in a wide frequency range. In addition, displacements due to the placement of ferrite material and the variation of the transfer distance between the transmitter and receiver units are investigated through practical measurements.